2022
DOI: 10.1155/2022/3378599
|View full text |Cite
|
Sign up to set email alerts
|

Application of Convolutional Neural Network-Based Hierarchical Teaching Method in College English Teaching and Examination Reform

Abstract: Along with the pace of educational reform in colleges and universities, a variety of new types of teaching and research approaches stand out in each subject taught in colleges and universities. For example, in college English lectures, given the practice of individualized tiered teaching, the development of relevant teaching models for students at different levels has become a new type of teaching and research developed year by year. Based on the English classroom program, teachers should make cognizance of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In particular, the influence that the internal factor of academic buoyancy plays in the relation between the support in EFL class and learning burnout remains unclear. In addition, considering that many universities in China have implemented tiered teaching for EFL learners to maximize teaching and learning effectiveness (Zhang & Huang, 2022), and that prior research has found that school levels diverged on the role of social support in burnout (Kim et al, 2018), this research wonders whether class level with regard to the degree of English proficiency can be a potential moderator to further explain the effects of targeted antecedents on learning burnout. Therefore, the study of various factors, including social support supplied by teachers and peers in EFL class, academic buoyancy, class level, and learning burnout, among Chinese EFL learners in their unique tertiary learning context would hopefully provide novel and interesting insights.…”
Section: Most Relevant Publicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the influence that the internal factor of academic buoyancy plays in the relation between the support in EFL class and learning burnout remains unclear. In addition, considering that many universities in China have implemented tiered teaching for EFL learners to maximize teaching and learning effectiveness (Zhang & Huang, 2022), and that prior research has found that school levels diverged on the role of social support in burnout (Kim et al, 2018), this research wonders whether class level with regard to the degree of English proficiency can be a potential moderator to further explain the effects of targeted antecedents on learning burnout. Therefore, the study of various factors, including social support supplied by teachers and peers in EFL class, academic buoyancy, class level, and learning burnout, among Chinese EFL learners in their unique tertiary learning context would hopefully provide novel and interesting insights.…”
Section: Most Relevant Publicationsmentioning
confidence: 99%
“…These findings motivated us to consider the role of class level when we proposed our conceptual model. Given that the university where this research was conducted has adopted the EFL tiered-teaching mode, as have many universities in China (Zhang & Huang, 2022), the EFL course was conducted in classes that included learners with varying degrees of English proficiency. The placement was determined initially based upon the results of students' EFL entrance exam and changes could be made at the end of each semester according to the students' performance.…”
Section: The Role Of Class Levelmentioning
confidence: 99%